Determining inherent deformations of HSLA steel T-joint under structural constraint by means of thermal elastic plastic FEM. (February 2020) - Liang, Wei; Hu, Xing; Zheng, Ying; Deng, Dean
Abstract: The inherent strain method is a powerful and efficient tool to simulate welding deformation, so it recently becomes the mainstream way to estimate the total welding distortion of large complex welded structures. When using this method to predict welding deformation, the simulated result strongly depends on the accuracy of the inherent deformations of each typical joint involved in the welded structure. During welding process, the constraint condition usually has a significant influence on the inherent deformations of a welded joint. In the current study, the influence of different constraint conditions on the inherent deformations of atypical high strength low alloy steel thin-plate T-joint was investigated experimentally and numerically. Meanwhile, the welding deformation of a simple thin-plate stiffened-panel structure was calculated by using the inherent deformations of T-joints with different constraint conditions. Based on the simulated results, the influence of the inherent deformations of T-joints with different restraint conditions on the total welding deformation of the stiffened-panel structure was clarified. In addition, a newly method was proposed to obtain the inherent deformations of a welded joint with structural constraint condition. Highlights: The influence of constraint condition on the inherent deformations of high strength low alloy steel T-joint was clarified. An elastic FEM based on inherent strain theory has been developed using ABAQUS software. A newly approach has been proposed to obtain the inherent deformations of a joint with structural constraint.